Immunotherapy for Refractory Autoimmune Encephalitis - Yang, Jiawei; Liu, Xueyan (Frontiers in Immunology, 2021)
Autoimmune encephalitis (AE) is an immune-mediated disease involving the central nervous system, usually caused by antigen-antibody reactions. With the advent of autoantibody-associated diseases, AE has become a hot research frontier in neuroimmunology. The first-line conventional treatments of autoimmune encephalitis consist of steroids, gammaglobulins, plasmapheresis, and second-line therapy includes rituximab. Despite considerable research and expanding clinical experience, current treatments are still ineffective for a significant number of patients. Although there is no clear consensus and clinical trial evidence limited, third-line therapy is a viable alternative for refractory encephalitis patients. With the current rapid research progress, a breakthrough in the treatment of AE is critical. This article aims to review the third-line therapy for refractory AE